Observation of Observation Results, Mathematics Learning Conducted at Tkq As-Suhriyah - Laila Zulfah Laila23 (Universitas muhammadiyah Banjarmasin, 2022)
ABSTRACT This observational study aims to determine the learning system carried out at TKQ As-Suhriyah. In studying mathematics, are children able to understand the mathematics lessons given by the teacher. Mathematics learning given at the early childhood level is still non-formal, where children have not been fully provided with actual mathematical material but are only introductory. . In mathematics education, for example in number recognition, numbers are first heard by mentioning the numbers one, two, three and so on. And show objects totaling one, two, three and so on, it doesn't mean the material immediately introduces the number symbol